Surveying Critical Thinking Dispositions between Freshmen and Senior Students in School of Allied Medical Sciences in 2012-2013 Academic Year - Abolfazl Taheri; Fereydoon Azadeh; Mohammad Moradi-Joo; Omid Yousefianzadeh (Tehran University of Medical Sciences, 2017)
Background and Aim: In medical sciences, students need problem-solving and decision-making abilities to cure diseases. The present study aims to survey the critical thinking disposition between freshman and senior students in School of Allied Medical Sciences in 2012- 2013 academic year. Materials and Methods: In this descriptive cross-sectional study, 250 students were selected randomly and their critical thinking disposition was assessed. "The Ricketts critical thinking disposition scale (2003)" consists of 33 multiple choice questions; the scale was used by the researcher to assess the critical thinking disposition. Finally, the data was analyzed by t-test and ANOVA using SPSS software. Results: The mean of students' critical thinking disposition was 3.54 which shows that this ability was on the average among students. Also, the t-test results showed that there was a difference between freshmen and seniors. The critical thinking disposition was compared between students in various fields; the results did not reveal a significant difference.    Conclusion: In spite of the high critical thinking disposition achieved by senior students and the similar guidance in different fields of study for enhancing the disposition, the variable is not at the ideal and expected level. Therefore, it is necessary to use certain materials and measures in educational planning so that the disposition level can get close to the ideal level.